2013
DOI: 10.1371/journal.pone.0061773
|View full text |Cite
|
Sign up to set email alerts
|

Serine Proteolytic Pathway Activation Reveals an Expanded Ensemble of Wound Response Genes in Drosophila

Abstract: After injury to the animal epidermis, a variety of genes are transcriptionally activated in nearby cells to regenerate the missing cells and facilitate barrier repair. The range and types of diffusible wound signals that are produced by damaged epidermis and function to activate repair genes during epidermal regeneration remains a subject of very active study in many animals. In Drosophila embryos, we have discovered that serine protease function is locally activated around wound sites, and is also required fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
51
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(54 citation statements)
references
References 79 publications
2
51
1
Order By: Relevance
“…Our results and those of others highlight that, not only the induction of wound healing responses, but also the confinement of the responses to wound vicinity is under strict genetic control in flies (Juarez et al, 2011;Patterson et al, 2013). While cell fusion, in combination with cell growth, is critically required for epidermal wound closure (Losick et al, 2013), whether too much cell fusion is harmful to proper wound healing is unclear.…”
Section: Discussionmentioning
confidence: 63%
“…Our results and those of others highlight that, not only the induction of wound healing responses, but also the confinement of the responses to wound vicinity is under strict genetic control in flies (Juarez et al, 2011;Patterson et al, 2013). While cell fusion, in combination with cell growth, is critically required for epidermal wound closure (Losick et al, 2013), whether too much cell fusion is harmful to proper wound healing is unclear.…”
Section: Discussionmentioning
confidence: 63%
“…Surprisingly, in this context, spz function was not required (19). Other studies in late stage embryos revealed that clean puncture wounding results in the transcriptional activation of the dorsal and spz genes in epidermal cells adjacent to wounds (20), suggesting their involvement in epidermal wound healing, perhaps in an autoregulatory circuit involved in wound repair.…”
mentioning
confidence: 72%
“…Our previous research showed that serine protease function is required and sufficient to activate certain epidermal barrier repair genes after puncture wounding of late stage embryos (20). The activation of epidermal barrier repair genes has been shown to require different combinations of transcription factors (11,12); however, the entire range of signaling pathways genetically required for proper barrier regeneration is still unknown.…”
Section: Significancementioning
confidence: 99%
See 1 more Smart Citation
“…Our findings extend this theory by showing that Psh is responsible for endogenous DAMP-mediated systemic activation of Toll signaling. The activation of innate immunity-regulated genes including Drs and Mtk was previously observed following serine protease activation in response to wound stimulation (56). Serine protease(s) released from necrotic cells may act to initiate the Psh-dependent Toll signaling pathway.…”
Section: Discussionmentioning
confidence: 90%